Fire Occurrence Mediates Small-Mammal Seed Removal of Native Tree Species in a Neotropical Savanna - Cazetta, Thayse Cavicchioli; Vieira, Emerson M. (Frontiers in Ecology and Evolution, 2021)
Seed dispersal and predation are critical processes for plant recruitment which can be affected by fire events. We investigated community composition of small mammals in gallery forests with distinct burning histories (burned or not burned ~3 years before) in the Cerrado (neotropical savanna). We evaluated the role of these animals as seed removers of 6 native tree species, potentially mediated by the occurrence of fire. We sampled 4 previously burned sites and 4 unburned ones. Seed removal was assessed using 2 exclusion treatments: exclusive access of small rodents and access of all seed-removing vertebrates. The previous burning changed the structural characteristics of the forests, increasing the density of the understory vegetation and herbaceous cover, which determined differences in species composition, richness, and abundance of small rodents (abundance in the burned forests was 1/6 of the abundance in the unburnt ones). Seed removal rates across the 6 species were reduced in burnt forests in both treatments and were higher for the ‘all vertebrates’ treatment. Other vertebrates, larger than small rodents, played a significant role as seed removers for 5 of the 6 species. The effects of fire were consistent across species, but for the 2 species with the largest seeds (Hymenaea courbaril and Mauritia flexuosa) removal rates for both treatments were extremely low in the burned forests (≦ 5%). The observed decline in small rodent seed predation in the burned forests may have medium to long-term consequences on plant communities in gallery forests, potentially affecting community composition and species coexistence in these forests. Moreover, fire caused a sharp decline in seed removal by large mammals, indicating that the maintenance of dispersal services provided by these mammals (mainly the agouti Dasyprota azarae) for the large-seeded species may be jeopardized by the burning of gallery forests. This burning would also affect several small mammal species that occur in the surrounding typical savanna habitats but also use these forests. Fire events have been increasing in frequency and intensity because of human activities and climate changing. This current scenario poses a serious threat considering that these forests are fire-sensitive ecosystems within the Cerrado.